AYURVEDIC CONCEPT OF PREMENSTRUAL SYNDROME WITH SPECIAL REFERENCE TO PITTAVRITTA VYANA VAYU (International Journal of Ayurveda and Pharma Research, 2017)
Premenstrual Syndrome (PMS) refers to a complex of cyclical and recurrent physical, emotional and behavioral symptoms that occur specifically in luteal phase and remain for minimum three consecutive menstrual cycles. Up to 80% of women of child bearing age report with few mild symptoms of PMS prior to menstruation. But clinically significant PMS is seen only in 3 to 8% of women. Its more severe form, Premenstrual Dysphoric Disorder (PMDD) has listed one among the Depressive mental disorders by American Psychiatric Association. Premenstrual Syndrome, an often neglecting medical condition due to social taboo of not discussing the issue of menstruation, was not considered as a disease earlier due to unawareness of the grave symptoms of the disease. Till now, the disease is a medical mystery with unknown cause and without any specific proved diagnosis and medication in modern medicine. This article is merely an attempt to relate PMS with Pittavritta Vyana Vata, which is an Avaranajanya Vyadhi. In Rituvyateetakala which is compared mainly with the luteal phase, there is Pittakopavastha and Vatasanchayavastha. With excess intake of Pittakar Nidan in Rituvyateetakala, Sanchita Vata specifically Vyana Vayu gets Avritta with Kupita Pitta and manifested in the form of Sarvanga Daha, Santapa, Klama etc. So the disease PMS can be managed and treated on the line of Pittavritta Vyana Vayu so as to provide relief from its deleterious effects and improve her family and social life.